Oxford handbook of gastrointestinal nursing - Burch, Jennie; Collins, Brigitte (Oxford : Oxford University Press, 2021)
This practical handbook is a comprehensive guide to the nursing care and management of gastrointestinal patients. It has been thoroughly revised and standardised to ensure it is up to date and easy to use.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 18, 2021).
Keywords: Gastrointestinal system -- Diseases -- Nursing